Differential executive functioning in the topology of Spirit possession or dissociative disorders: an explorative cultural study - Samir Al-Adawi (711559) (2022)
Background In Oman, anecdotal and impressionistic observation have helped parse and categorize various manifestations of spirit possession into two broad and distinct categories: intermittent dissociative phenomenon and transitory dissociative phenomenon. The primary aim of the present study was to compare the performance of participants on neuropsychological tests among different grades of possession. Other correlates were also sought. Methods Assessment criteria for the two groups included measures examining executive functioning: controlled oral word association test Verbal Fluency, Wisconsin Card Sorting Test (Perseverative error and the number of categories achieved), Trail Making Test and the Tower of London Test (number of correctly solved problems). Sociodemographic variables and the history of trauma were also sought. Result Among 84 participants, one third of them presented the intermittent possession type and two thirds, the transitory possession type. Their mean age was 34.17 ± 11.82 and 56% of them were female. Nearly 35% of them endorsed a history of a traumatic experience. Both the multivariate models showed statistical significance (F (5, 78) = 5.57, p < 0.001, R2 = 0.22), F (5, 78) = 11.38, p < 0.001, R2 = 0.39) with an independent predictor of intermittent dissociative phenomenon (β = − 3.408, p < 0.001), (β = 63.88, p < 0.001) for Verbal Fluency and Trail Making Test, respectively. The history of the traumatic event was also statistically significant with the results of the Trail Making Test (β = − 26.01, p < 0.041. Furthermore, the subtype of Pathogenic Possession turned out to be an independent predictor across all models: Wisconsin Card Sorting Test perseverative error, Wisconsin card sorting test categories achieved and the number of problems solved in the Tower of London Test (OR = 3.70, 95% C.I. 2.97–4.61; p < 0.001), (OR = 0.57, 95% C.I.0.39–0.84; p = 0.004) and (OR = 0.80, 95% C.I. 0.65–0.99; p < 0.037) respectively. Conclusions This study suggests that typology of spirit possession found in Oman tends to differ on indices of executive function. Those with ‘diagnosis’ of intermittent possession showed impairment in many indices of executive functioning. Despite its wide prevalence, spirit possession has not been examined in terms of its neuropsychological functioning. We believe that this study will be instrumental in laying the groundwork for a more robust methodology. Other Information Published in: BMC Psychiatry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1186/s12888-019-2358-2